1989
DOI: 10.4315/0362-028x-52.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Drying Injury of Lactobacillus Acidophilus

Abstract: Lactobacillus acidophilus ATCC 4355 cells were more stable to freezing at −20°C after supplementation of the growth medium with 0.1% CaCO3. However, added calcium did not affect viability and injury during lyophilization. Inclusion of 5% glycerol in the suspending medium before freeze-drying resulted in superior survival and decreased injury during the drying process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Culture dehydration of L. acidophilus was normally performed by freeze-drying which might cause damage to cells owing to the freezing and subsequent drying treatment (Bozoglu and Gurakan, 1989;Champagne et al, 1991;Marth, 1973). The culture might be mixed with some protectants in order to improve survival during the drying process (Potts, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Culture dehydration of L. acidophilus was normally performed by freeze-drying which might cause damage to cells owing to the freezing and subsequent drying treatment (Bozoglu and Gurakan, 1989;Champagne et al, 1991;Marth, 1973). The culture might be mixed with some protectants in order to improve survival during the drying process (Potts, 1994).…”
mentioning
confidence: 99%
“…The cell pellets were then suspended in 10 ml protective media to make concentrated cell suspensions of about 10 9 -10 10 cells/ml for the experiments. Three different protective media were used for experiments: (1) 10% NFDMS was used as the basal medium for drying without protectants (Bozoglu and Gurakan, 1989;King and Su, 1993), (2) 4.15% glycerol and 10.08% NFDMS for freeze-drying, and (3) 4.10% glycerol and 10.71% NFDMS for CLTVD with protectants based on the optimum conditions obtained by King and Lin (1995).…”
mentioning
confidence: 99%
“…Comparative studies have shown preserved acidification capacity for 2-16 hours when applied directly, though with a certain delay in the first hours. Other authors also mention relatively weak changes in the acidification capacity of frozen or freeze-dried concentrates of lactic acid bacteria (2,5,7,8).…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion of 5% glycerol also provided a survival of 98% and was better than a combination of 0.5% NH,CI + 10% sucrose + 0.5% ascorbate. On the other hand, the injured fraction drastically increased after freeze drying in all conditions, except for glycerol supplementation, which could ensure a survival ratio of 57% (Bozogu and Gurakan, 1989).…”
Section: Foodstuffs Fodders and Beveragesmentioning
confidence: 97%